Finerenone Attenuates Endothelial Dysfunction and Albuminuria in a Chronic Kidney Disease Model by a Reduction in Oxidative Stress - González-Blázquez, Raquel; Somoza, Beatriz; Gil-Ortega, Marta; Martín Ramos, Miriam; Ramiro-Cortijo, David; Vega-Martín, Elena; Schulz, Angela; Ruilope, Luis Miguel; Kolkhof, Peter; Kreutz, Reinhold; Fernández-Alfonso, María S. (Frontiers in Pharmacology, 2018)
Albuminuria is an early marker of renovascular damage linked to an increase of oxidative stress. The Munich Wistar Frömter (MWF) rat, a model of chronic kidney disease, exhibits endothelial dysfunction associated to reduced nitric oxide bioavailability. We hypothesize that the new highly selective, non-steroidal mineralocorticoid receptor antagonist, finerenone, reverses both endothelial dysfunction and microalbuminuria. Twelve-week-old MWF (MWF-C; MWF-FIN) and aged-matched normoalbuminuric Wistar (W-C; W-FIN) rats were treated with finerenone (FIN, 10 mg/kg/day p.o.) or vehicle (C) for 4-weeks. Systolic blood pressure (SBP) and albuminuria were determined the last day of treatment. Finerenone lowered albuminuria by >40% and significantly reduced SBP in MWF. Aortic rings of MWF-C showed higher contractions to either noradrenaline (NA) or angiotensin II (Ang II), and lower relaxation to acetylcholine (Ach) than W-C rings. These alterations were reversed by finerenone to W-C control levels due to an upregulation in phosphorylated Akt and eNOS, and an increase in NO availability. Apocynin and 3-amino-1,2,4-triazole significantly reduced contractions to NA or Ang II in MWF-C, but not in MWF-FIN rings. Accordingly, a significant increase of Mn-superoxide dismutase (SOD) and Cu/Zn-SOD protein levels were observed in rings of MWF-FIN, without differences in p22phox, p47phox or catalase levels. Total SOD activity was increased in kidneys from MWF-FIN rats. In conclusion, finerenone treatment improves aortic endothelial dysfunction through an increase in NO availability due to an upregulation in SOD activity and a decrease in superoxide anion levels. This is associated with an increase in renal SOD activity and a reduction of albuminuria.